PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS III SDN 19 SANTUR KOTA SAWAHLUNTO - Sakinah Handriah, Tengku; Yesni Yenti; Muhammadi; Ummiatul Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
his classroom action research aimed to improve students' learning outcomes in Integrated Science and Social Studies (IPAS) through the implementation of the Problem Based Learning (PBL) model in Grade III of SDN 19 Santur, Sawahlunto. The study was conducted because students' learning outcomes were still below the minimum mastery criteria, and the learning process remained teacher-centered, resulting in low student participation and critical thinking skills. The research employed a qualitative and quantitative approach using the Classroom Action Research (CAR) design, which consisted of two cycles. Each cycle included four stages: planning, implementation, observation, and reflection. The research subjects were 18 third-grade students. Data were collected through observation sheets, learning outcome tests, documentation, and field notes, and were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the implementation of the Problem Based Learning model improved both the quality of the learning process and students' learning outcomes. Students became more actively involved in identifying problems, discussing solutions collaboratively, and presenting the results of their investigations. Furthermore, improvements were observed in the cognitive, affective, and psychomotor domains across each cycle. Therefore, the Problem Based Learning model proved to be effective in enhancing learning outcomes in IPAS learning for third-grade elementary school students.